Identification of a hydrogen transfer model with dynamical boundary conditions - Yury V. Zaika (International Journal of Mathematics and Mathematical Sciences)
The nonlinear inverse problem of determining the hydrogen permeability parameters of stratified materials is considered. The model includes diffusion, invertible capture and sorption/desorption processes on surface, which leads to dynamical boundary conditions. For the concentration impulses method, the equation of stationary oscillations of concentration is obtained. Parametric identification scheme of the model is proposed. Techniques of Fourier series and conjugate equations are used.